GAMBARAN KELUHAN OTOT ANTARA SCHOOL FROM HOME DAN WORK FROM HOME DALAM PANDEMI COVID-19 - Bayu Yoni Setyo Nugroho; Evina Widianawati; Widya Ratna Wulan (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Background: School from Home and Work from Home were activities carried out by students and employees during the COVID-19 pandemic. Activities aimed to comply with health protocols and social distancing to prevent transmission of the COVID-19 virus. Students and employees who studied and worked from home had one health risk, muscle disorders complaints caused by the use of equipment or facilities that were not ergonomic. Muscle complaints, when not handled properly, would reduce productivity in studying and working. The purpose of this study was to find out a description of the location and types of muscle pain complaints experienced by students and workers during the pandemic. Methods:this study used a Nordic Body Map questionnaire and an online questionnaire.The study design used cross-sectional descriptive approach respondents with 25 students and 25 employees. Results: Complaints of neck pain were the most common complaints experienced by students and workers who implemented SFH and WFH.Keywords: Musculoskeletal, School From Home, Work From Home